Openness in Social Media as a Form of Symbolic Interaction in the Digital Era - Ramadani, Naisya Insani; Muhammad, Achmad Hufad; Achdiani, Yani (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Social media has become a space for self-expression that allows individuals to display their personal sides more openly than in real life. This phenomenon shows a shift in communication patterns related to identity management, the search for social recognition, and the need for security. This study aims to explore the factors that influence openness on social media and its impact on individual social and psychological conditions. The method used is a qualitative approach with an open-ended questionnaire instrument distributed to social media users. The results showed that openness is influenced by emotional comfort, perception of the audience, and control over the information shared. However, openness also poses risks such as privacy violations and social pressure, especially when the responses received are negative. The findings emphasize the importance of reflective awareness in sharing personal information to keep social media use healthy and responsible.